Analisis Manajemen Keuangan Perolehan dan Pengelolaan Panti Asuhan Terhadap Kesejahteraan Anak: Studi Kasus pada Panti Asuhan Al-Kahfi Surabaya - Arma Yuli Fitriasari; Hwihanus Hwihanus (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research analyzes the financial management of the acquisition and management of orphanages on the welfare of children at the Al-Kahfi orphanage located in Surabaya. The aim of this research is to answer how the financial management of the orphanage acquires and manages it, whether the implementation of financial reports is in accordance with the principles of financial reporting, how the orphanage evaluates the impact of their financial management on the welfare of the children. The research method used is qualitative using data triangulation. The result obtained is that the orphanage receives fixed funds from each household and then these funds are used for the children's needs. The application of financial reports for orphanages is in accordance with accounting standards. The impact of its management on children's welfare, children can go to school and children's rights are fulfilled.